Willingness-to-use and preferences for model-informed antenatal doses: a cross-sectional study among European healthcare practitioners and pregnant women - Koldeweij, C. J. M.; Dibbets, A. C.; Ceulemans, M.; de Vries, L. C.; Franklin, B. D.; Scheepers, H. C. J.; de Wildt, S. N. (Frontiers in Pharmacology, 2024)
Background: Physiological changes in pregnancy may affect drug safety and efficacy, sometimes requiring dose adjustments. Pregnancy-adjusted doses, however, are missing for most medications. Increasingly, pharmacokinetic models can be used for antenatal dose finding. Given the novelty of this technique and potential concerns about dose credibility, the acceptability of model-informed antenatal doses should be explored. Objective: We aimed to assess the willingness-to-use and preferred features for model-informed antenatal doses among healthcare practitioners (HCPs) and pregnant women in multiple European countries. Methods: A crosssectional, web-based study drawing on two open surveys was performed between 8 September and 30 November 2022. Each survey comprised statements drawn from prior focus groups, associated with Likert-scales. Themes included respondents' information needs, search behaviours along with their willingness-to-use and preferred features for model-informed antenatal doses. The surveys were disseminated through professional societies, pregnancy websites and social media. A descriptive analysis was performed. Results: In total, 608 HCPs from different specialties and 794 pregnant women across 15 countries participated, with 81% of respondents across both groups in the Netherlands or Belgium. Among pregnant women, 31% were medical professionals and 85% used medication during pregnancy. Eighty-three percent of HCPs found current antenatal pharmacotherapy suboptimal and 97% believed that modelinformed antenatal doses would enhance the quality of antenatal care. Most HCPs (93%) and pregnant women (75%) would be willing to follow model-informed antenatal doses. Most HCPs desired access to the evidence (88%), including from pharmacokinetic modelling (62%). Most pregnant women (96%) wanted to understand antenatal dosing rationales and to be involved in dosing decisions (97%). Conclusion: The willingness-to-use model-informed antenatal doses is high among HCPs and pregnant women provided that certain information needs are met.